Opportunity denied : limiting Black women to devalued work - Branch, Enobong Hannah, 1983- (Rutgers University Press, 2011)
Opportunity Denied is the first comprehensive look at changes in race, gender, and women's work across time, comparing the labor force experiences of Black women to White women, Black men and White men. From free Black women in 1860 to Black women in 2008, the experience of discrimination in seeking and keeping a job has been determinedly constant. Branch focuses on occupational segregation before 1970 and situates the findings of contemporary studies in a broad historical context, illustrating how inequality can grow and become entrenched over time through the institution of work.